DNA Cloning and Assembly Methods - Valla, Svein.; Valla, Svein.; Lale, Rahmi.; Lale, Rahmi. (Methods in Molecular Biology, 2014)
In DNA Cloning and Assembly Methods, expert researchers in the field detail many of the methods which are now commonly used for DNA cloning and make cloning procedures faster, more reliable and also suitable for high-throughput handling. These include methods and protocols that are based on several mechanisms including type II and IIS restriction enzymes, single stranded annealing, sequence overlap, and recombination. With additional chapters on software programs that are suitable for primer design, a feature crucial for the functionality of the described methods. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, DNA Cloning and Assembly Methods seeks to provide  scientist with a valuable and useful resource for wet lab researchers within life sciences.